Application of Management Information Systems in Road Infrastructure Management (Proceedings of Faculty of Civil Engineering, 2023)
In the field of spatial management, especially from the point of view of spatial economics, many decisions have long-term effects on the environment. Therefore, it is essential that the boundary conditions of the decision-making process are not only transparent, but also aligned with the sustainable development goals. At the same time, road infrastructure represents one of the most complex linear structures in the area, and its comprehensive management should respond to various types of problems, from structured to unstructured, which occur at all levels of decision-making. To solve such problems, management information systems (UIS) can help decision-makers to apply appropriate models and methods during the decision-making process. This paper provides an overview of the different types of UIS that can be used in road infrastructure management. The method of selecting an appropriate UIS and the method of interaction between data and models in such a management system are also discussed.
Keywords: management information systems; decision making; project management; road infrastructure